Coaching-Mentoring Supervision in Islamic Education: Enhancing Teaching Quality for the SDGs - Rina Murtyaningsih; Yeri Utami; Neil C. Cranston (Profetika: Jurnal Studi Islam, 2025)
Objective: This study aims to analyse the effectiveness of coaching-mentoring-based IRE teaching supervision in improving the quality of teachers' teaching practices. The focus of the research includes strengthening teachers' pedagogic and spiritual competence as well as changing supervisory relationships to collaborative. This study is also linked to the achievement of SDG 4 on quality education. Theoretical framework: This research is based on the theory of empowerment supervision, reflective learning, and continuous professional development. The coaching-mentoring approach is understood as a dialogical supervision strategy that places the teacher as a reflective partner. This framework is in line with SDG 4.c and SDG 4.7 in the context of Islamic education. Literature review: The literature shows that traditional evaluative supervision is less effective in encouraging changes in teachers' teaching practices. The coaching and mentoring approach has been proven to increase reflection, collaboration, and pedagogic innovation. However, the study of IRE supervision based on coaching-mentoring that is integrated with the SDGs is still limited. Methods: This study uses a qualitative approach with a case study design. Data was collected through interviews, observations, and documentation at SMK Muhammadiyah 1 Blora. The analysis was carried out thematically. Results: The results showed that coaching-mentoring supervision improved teacher reflection, pedagogic and spiritual competence, and authentic assessment practices. The supervisor-teacher relationship has become more collaborative and supportive. This approach also builds a collaborative and sustainable school culture. Implications: Effective coaching-mentoring supervision as a model of professional development of IRE teachers. This approach needs to be integrated into the school supervision system. This model supports the achievement of SDG 4. Novelty: This research integrates coaching-mentoring-based IRE supervision with the perspective of SDGs. Focus on pedagogic and spiritual development at the same time. This model is relevant for continuous Islamic education.